Superior Intratumoral Penetration of Paclitaxel Nanodots Strengthens Tumor Restriction and Metastasis Prevention. Issue 21 (12th February 2015) - Ni, Dezhi; Ding, Hui; Liu, Shan; Yue, Hua; Bao, Yali; Wang, Zhenhua; Su, Zhiguo; Wei, Wei; Ma, Guanghui
<x xml:space="preserve">Abstract</x> Recently discovered intratumoral diffusion resistance, together with poor solubility and nontargeted distribution of chemotherapeutic drugs, has significantly impaired the performance of cancer treatments. By developing a well‐designed droplet‐confined/cryodesiccation‐driven crystallization approach, we herein report the successful preparation of nanocrystallites of insoluble chemotherapeutic drug paclitaxel (PTX) in forms of nanodots (NDs, ≈10 nm) and nanoparticles (NPs, ≈70 nm) with considerably high drug loading capacity. Superficially coated Pluronic F127 is demonstrated to endow the both PTX nanocrystallites with excellent water solubility and prevent undesired phagocyte uptake. Further decoration with tumor‐penetrating peptide iRGD, as expected, indiscriminatively facilitates tumor cell uptake in traditional monolayer cell culture model. On the contrary, distinctly enhanced performances in inward penetration and ensuing elimination of 3D multicellular tumor spheroids are achieved by iRGD‐NDs rather than iRGD‐NPs, revealing the significant influence of particle size variation in nanoscale. In vivo experiments verify that, although efficient tumor enrichment is achieved by all nanocrystallites, only the iRGD‐grafted nanocrystallites of ultranano size realize thorough intratumoral delivery and reach cancer stem cells, which are concealed inside the tumor core. Consequently, much strengthened restriction on progress and metastasis of orthotopic 4T1 mammary adenocarcinoma is achieved in murine model, in sharp contrast to commercial PTX formulation Taxol.